Outside versus inside the home: Tensions between fathers’ work and parenting responsibilities in Tanzania - Sein Kim; Juliet K. McCann; Damas Joachim; Mary Kabati; Joshua Jeong (PLoS ONE, 2026)
Globally, mothers are disproportionately responsible for childcare, while fathers are predominantly viewed as breadwinners. Although recent studies reveal that fathers are becoming more engaged in parenting, little is known about the broader contexts surrounding how fathers allocate their time between parenting, income-generating work, and other daily activities. The objective of this study was to characterize the typical daily schedules from morning to evening among fathers with young children under aged 2 years. Additionally, we aimed to identify the perceived barriers and facilitators influencing fathers’ time spent on parenting. We conducted 60 in-depth interviews (29 fathers and 23 mothers and 8 community stakeholders) and 9 focus group discussions (3 with fathers only, 2 with mothers only, and 4 mixed parent groups) across 4 purposively sampled, peri-urban communities in Mwanza, Tanzania. Among a subsample of 14 fathers, we revisited and conducted follow up in-depth interviews to further obtain retrospective hourly accounts of fathers’ daily time use. Data were analyzed using both deductive and inductive approaches. Overall, fathers spent most daytime hours out of the home engaging in work-related activities, and evenings were often a time when some fathers socialized with peers. Approximately half of fathers reported some involvement in parenting, childcare, or household chores. However, these activities were generally brief and concentrated at specific times of day, such as early mornings before fathers left for work, during lunchtime when men returned home, or on weekends when men spent more time at home. Key barriers to fathers’ time allocation to parenting included patriarchal gender norms that frame childcare as primarily women’s responsibility, poverty, and work-related stress. Facilitators of fathers’ time towards parenting included greater autonomy over work schedules and positive attitudes valuing fathers’ nurturing care roles. These findings provide important insights into fathers’ daily routines in this context and the social, cultural, and structural factors that enable or constrain their engagement in parenting. By illuminating men’s time use patterns, this study offers evidence to inform the design of parenting programs that are more responsive to fathers’ schedules and constraints and ultimately promote greater father engagement in childcare.